2011
DOI: 10.1021/ja204200x
|View full text |Cite
|
Sign up to set email alerts
|

Nongenetic Reprogramming of a Fungal Highly Reducing Polyketide Synthase

Abstract: The biosynthesis of the fungal metabolite tenellin from Beauveria bassiana CBS110.25 was investigated in the presence of the epigenetic modifiers 5-azacytidine and suberoyl bis-hydroxamic acid and under conditions where individual genes from the tenellin biosynthetic gene cluster were silenced. Numerous new compounds were synthesized, indicating that the normal predominant biosynthesis of tenellin is just one outcome out of a diverse array of possible products. The structures of the products reveal key clues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 35 publications
2
38
2
Order By: Relevance
“…In contrast, genetic analyses of the biosynthetic pathway of the 2-pyridone tenellin revealed that this compound does not appear to contribute to B. bassiana virulence (40,41). This system also has been exploited for novel compound discovery, with expression of the tenellin nonribosomal peptide synthase in Aspergillus oryzae leading to the production of several new compounds and the use of chemical epigenetic modifiers in B. bassiana altering the selectivity of tenellin polyketide synthase to produce different products (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, genetic analyses of the biosynthetic pathway of the 2-pyridone tenellin revealed that this compound does not appear to contribute to B. bassiana virulence (40,41). This system also has been exploited for novel compound discovery, with expression of the tenellin nonribosomal peptide synthase in Aspergillus oryzae leading to the production of several new compounds and the use of chemical epigenetic modifiers in B. bassiana altering the selectivity of tenellin polyketide synthase to produce different products (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…There is no obvious remnants of an inactive enoylreductase (ER°) domain or a methyltransferase (CMeT) domain, as seen in several iterative fungal PKS-NRPS with the similar organization, such as PKS for tenellin, lovastain, and compactin. [24-27] . Although this type of iterative PKS-NRPS is commonly seen in fungi, it is not common in bacteria until recent years.…”
mentioning
confidence: 99%
“…Fungal iPKSs may be classified into three subgroups (5). Highly reducing iPKSs (hrPKSs) generate complex linear or nonaromatic cyclic products by reducing the nascent β-ketoacyl intermediates to the β-alcohol, the alkene, or the alkane after each condensation step using their ketoreductase, dehydratase, and enoyl reductase domains to execute a cryptic biosynthetic program (2,(6)(7)(8). Partially reducing iPKSs omit enoyl reduction to generate simple cyclic structures (5).…”
mentioning
confidence: 99%